"\\left(1+2xy\\:cos\\:x^2\\:-2xy\\right)dx+\\left(sinx^2-x^2\\right)d\\:y=0"
"\\left(1+2xy\\cos \\left(x^2\\right)-2xy\\right)dx+\\left(\\sin \\left(x^2\\right)-x^2\\right)dy=0"
First order linear Ordinary Differential Equation
"\\mathrm{A\\:first\\:order\\:linear\\:ODE\\:has\\:the\\:form\\:of\\:}y'\\left(x\\right)+p\\left(x\\right)y=q\\left(x\\right)"
Let y be the dependent variable, Divide by dx:
"1+2xy\\cos \\left(x^2\\right)-2xy+\\left(\\sin \\left(x^2\\right)-x^2\\right)\\frac{dy}{dx}=0"
"\\mathrm{Substitute\\quad }\\frac{dy}{dx}\\mathrm{\\:with\\:}y'"
"1+2xy\\cos \\left(x^2\\right)-2xy+\\left(\\sin \\left(x^2\\right)-x^2\\right)y'\\:=0"
We rewrite in the form of a first order linear ODE
"y'\\:+\\frac{2x\\left(\\cos \\left(x^2\\right)-1\\right)}{-x^2+\\sin \\left(x^2\\right)}y=-\\frac{1}{\\sin \\left(x^2\\right)-x^2}"
We find integration factor: "\\mu = -x^2 + \\sin \\left(x^2\\right)"
We put the equation in the from "(\\mu(x)\u22c5y)' = \\mu(x) \u22c5 q(x); ((-x^2 + sin(x^2))y)' = -1"
We solve:
"((-x^2 + sin(x^2))y)' = -1;\\,\n y=-\\frac{x}{-x^2+\\sin \\left(x^2\\right)}+\\frac{c_1}{-x^2+\\sin \\left(x^2\\right)}"
"y=-\\frac{x}{-x^2+\\sin \\left(x^2\\right)}+\\frac{c_1}{-x^2+\\sin \\left(x^2\\right)}"
Comments
Dear Amjad Ali Khan, please use the panel for submitting new questions.
Dy/dx=(2xycosx^2-2xy-1)/(x^2-sinx^2-3) ?
Leave a comment